(untitled) (Research, Society and Development, 2021)
The development of bioactive surgical additives to regulate inflammation and increase the speed of the healing process is one of the great challenges of clinical research. Because in surgical procedures they often used techniques that, in most cases, were very invasive and caused discomfort to the patient. In this sense, platelet-rich fibrin (PRF) appears as a natural, viable and quite satisfactory alternative with favorable results and presenting low risks. The PRF (Fibrin Rich in Platelets) was developed by Choukroun for use in oral and maxillofacial surgery, and has several areas of application within dentistry, which can mention the bone increase in implantology, maxillary sinus lifting, alveolar transplantation, aesthetic periodontal surgery, among others. The following review is a literature review study on the properties of platelet-rich fibrin (PRF) applied to oral surgery-choukroun protocol, based on 24 selected articles from 40 researched articles focusing on its preparation, advantages and disadvantages of using it in clinical applications, especially its use in oral surgery.